2011
DOI: 10.1200/jop.2010.000015
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Health Care Professionals' Perceptions of the Use and Utility of a Symptom Assessment System for Oncology Patients

Abstract: Purpose: Despite growing implementation of electronic symptom assessment in oncology settings, few studies have described how standardized symptom assessment can enhance multidisciplinary care. The Edmonton Symptom Assessment System (ESAS) is a validated measure of symptom burden that has been adopted by Ontario's cancer centers to assess symptoms for patients with cancer. This study examines the perceived value of the ESAS among clinical teams and barriers to its use in enhancing multidisciplinary care.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 21 publications
4
41
0
4
Order By: Relevance
“…In a pilot study implementing the ESAS in hospice settings, HCPs [15] valued the ESAS for its brevity, practicality for identifying patient care issues, engagement of patients in symptom assessment and use as a teaching tool. A second study revealed that use of the ESAS led to improvements in patient care [29]. The clinical relevancy of the ESAS is further supported by a recent review of clinical instruments for hospice and palliative care [30].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In a pilot study implementing the ESAS in hospice settings, HCPs [15] valued the ESAS for its brevity, practicality for identifying patient care issues, engagement of patients in symptom assessment and use as a teaching tool. A second study revealed that use of the ESAS led to improvements in patient care [29]. The clinical relevancy of the ESAS is further supported by a recent review of clinical instruments for hospice and palliative care [30].…”
Section: Discussionmentioning
confidence: 86%
“…Some HCPs have suggested that the tool lacks clinical relevancy if other team members do not refer to the tool when deciding about treatment options [28]. Others have highlighted concerns regarding the lack of understanding regarding the tool's use, particularly with respect to frequency of assessments and the misinterpretation of numerical rating scales [15,29]. In one study [15], participants reported concerns about high symptom ratings being interpreted as poor quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations